Acceptability and feasibility of a low-cost, theory-based and co-produced intervention to reduce workplace sitting time in desk-based university employees. (December 2015) - Mackenzie, Kelly; Goyder, Elizabeth; Eves, Francis
Abstract Background Prolonged sedentary time is linked with poor health, independent of physical activity levels. Workplace sitting significantly contributes to sedentary time, but there is limited research evaluating low-cost interventions targeting reductions in workplace sitting. Current evidence supports the use of multi-modal interventions developed using participative approaches. This study aimed to explore the acceptability and feasibility of a low-cost, co-produced, multi-modal intervention to reduce workplace sitting. Methods The intervention was developed with eleven volunteers from a large university department in the UK using participative approaches and "brainstorming" techniques. Main components of the intervention included: emails suggesting ways to "sit less" e.g. walking and standing meetings; free reminder software to install onto computers; social media to increase awareness; workplace champions; management support; and point-of-decision prompts e.g. by lifts encouraging stair use. All staff (n  = 317) were invited to take part. Seventeen participated in all aspects of the evaluation, completing pre- and post-intervention sitting logs and questionnaires. The intervention was delivered over four weeks from 7th July to 3rd August 2014. Pre- and post-intervention difference in daily workplace sitting time was presented as a mean ± standard deviation. Questionnaires were used to establish awareness of the intervention and its various elements, and to collect qualitative data regarding intervention acceptability and feasibility. Results Mean baseline sitting time of 440 min/workday was reported with a mean reduction of 26 ± 54 min/workday post-intervention (n  = 17, 95 % CI = −2 to 53). All participants were aware of the intervention as a whole, although there was a range of awareness for individual elements of the intervention. The intervention was generally felt to be both acceptable and feasible. Management support was perceived to be a strength, whilst specific strategies that were encouraged, including walking and standing meetings, received mixed feedback. Conclusions This small-scale pilot provides encouragement for the acceptability and feasibility of low-cost, multi-modal interventions to reduce workplace sitting in UK settings. Evaluation of this intervention provides useful information to support participatory approaches during intervention development and the potential for more sustainable low-cost interventions. Findings may be limited in terms of generalisability as this pilot was carried out within a health-related academic setting.